Decorating and loading ghosts with allergens for allergen immunotherapy - Fanuel, Songwe (Hum Vaccin Immunother, 2017)
More than 25% of the global population has IgE mediated allergic diseases. Allergen immunotherapy (AIT) is the only available form of treatment that alters the underlying mechanism of IgE-mediated allergic diseases. AIT is aimed at desensitizing allergic individuals by repeatedly administering disease-causing allergens over a long period of time. Despite its proven efficacy in numerous clinical trials, the effectiveness of AIT still suffers some drawbacks due to the quality of allergens used and in particular the unavailability of efficient allergen delivery systems. Several studies have demonstrated that bacterial ghosts (BG) systems can be used to display and deliver antigens to their targets for the management of diseases. However, there is no report documenting the use of BG systems for immunotherapy of IgE-mediated diseases so far. Thus, in this review, we intend to discuss the potentialities of BG systems for displaying and delivering allergens for future management of IgE-mediated diseases.